Prediction and evaluation of greenhouse gas emissions for sustainable road transport within Europe. (July 2021) - Kazancoglu, Yigit; Ozbiltekin-Pala, Melisa; Ozkan-Ozen, Yesim Deniz
Highlights: Greenhouse gases (GHG) are one of the most important environmental problems, emphasizing the need to reduce the negative impacts. As one of the human activities, transportation has the highest impact on the increase in greenhouse gas emissions. This study aims to make a detailed analysis of GHG emissions in four European countries, according to different types of road transport vehicles. Implications are presented in order to reduce the GHG emissions. Abstract: Environmental pollution leads a rise in sustainable development problems. Greenhouse gases(GHG) are one of the most important barriers against to sustainable development and greener cities. When the causes of GHG are investigated, human activities appeared as one of the main reasons. As one of the human activities, transportation has the highest impact on the increase in GHG emissions in green cities. Of the different transportation modes such as air, railways, and road, this study focused on road transportation due to its greater impact when compared to others in terms of GHG emissions. GHG emission estimation should be the initial step to evaluate current status of countries. Therefore, this study aims to make detailed analysis of GHG emissions in four European countries, due to different types of road transport vehicles. Grey prediction is used to estimate the amount of GHG emissions for each road transport vehicle for each country. In conclusion, implications are presented in order to reduce the GHG emissions and to meet sustainable development conditions according to the numerical results of the estimation and it is aimed to prepare a base for new studies about GHG emissions in road transportation.